The effects of cultural factors on the language learning - Othman, Mohd Sukki (Human Resource Management Academic Research Society, 2022)
The study aims at identifying the cultural problems, encountered in the translation of Arabic proverbs into Malay and the influence of Arabic and Malay Culture in language learning. To master and understand any languages, students must understand the culture and environment that will help them in process of language learning. The significance of the study stems from the fact that the interrelation of culture and language is to the extent that many classifications of culture are based on linguistic factors. In this article, the cultures division is assessed on Malay and Arabic as they belong to different cultural types. So that, the article will discuss various cultural factors that effects on the language learning and the proverbs translation especially between Malay and Arabic languages. This is also to find out the similarities and differences between Arabic and Malay languages on that factor in terms of ecological and culture. Hence, this article also going to explore the comparison between the two languages in learning the proverb which is influenced by cultural factors. The methodology in translation that used in this study is semantic translation. In a semantic translation scenario, one strives to convey the syntactic and semantic structures of the source language in the target language. This method most closely reproduces the original text in a foreign language, while maintaining context and culture. Data of the study comprised Malay and Arabic proverbs. They were selected from Malay and Arabic books and online databases of proverbs. Translating the selected proverbs collides with many challenges, of which the cultural ones are observed as the most manifest. What adds to the translation challenges is the colloquialism of the proverbs, which gives them enough semantic, social, and cultural values that cannot be stripped or ignored in the literal translation of the proverbs. The paper concludes that differences in translations are associated with the metaphorical schemas of the Arabic and Malay proverbs, which are attributed to cultural differences of the two languages. At the end, there are suggestions for further relevant investigations.